Albert Camus : from the absurd to revolt - Foley, John (Acumen, 2008)
Adopting an interdisciplinary approach, encompassing philosophy, literature, politics and history, John Foley examines the full breadth of Camus¿s ideas to provide acomprehensive and rigorous study of his political and philosophical thought and a significant contribution to a range of debates current in Camus research. Foley argues that the coherence of Camu's thought can best be understood through a thorough understanding of the concepts of "the absurd" and "revolt" as well as the relation between them. The book includes a detailed discussion of Camu's writings for the newspaper Combat, a systematic analysis of Camu's discussion of the moral legitimacy of political violence and terrorism, a reassessment of the prevailing postcolonial critique of Camu's humanism, and a sustained analysis ofCamu's most important and frequently neglected work, L'Homme revolte (The Rebel).